IMPLEMENTASI METODE AL-HUSNA DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MEMBACA AL-QUR'AN - Lulu Lamaa Rohadatul Aisy; Mukhlis Fathurrahman; Uswatun Khasanah (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The purpose of this study was to determine the implementation of the Al-Husna method in increasing motivation and learning outcomes to read the Qur'an. The subject of this research is MIN 1 Sukoharjo. This research is aqualitative research. Observations, interviews and documentation are tools for data collection. Meanwhile, data analysis uses data reduction, data presentation and data verification. The result of this study is that the implementation of the Al-Husna method in increasing motivation and learning outcomes to read the Qur'an is by using the Al-Husna method book media. In order to make it easier for teachers to guide students, the teacher divides them into several groups. Then the Al-Husna method that was applied was very effective with an average of students reaching the target of 90% of the 29 total students. In addition to the Al-Husna method that can be said to be effective, it can also be seen that the motivation of students has increased, which can be proven by the enthusiasm of students who do not give up easily and are enthusiastic in participating in learning.